Cognitive Performance in Adolescence: Links With Early Maternal Stimulation and Children's Anxious Behaviors. Issue 7 (3rd October 2018) - Bucci, Colleen M.; Brumariu, Laura E.; Moore, Michael T.
Abstract: This study tested a developmental model of cognitive performance in adolescence and explored potential mechanisms explaining the relations of early maternal stimulation and children's anxious behaviors with adolescents' cognitive performance. We utilized the NICHD SECCYD dataset ( n = 1, 112). Measures included questionnaires, coded observations, and self-report measures from infancy to adolescence. Results revealed that children who experienced greater early maternal stimulation and less anxious behaviors had better cognitive performance at age 15. Children's English self-efficacy, the quality of child–teacher relationships, and children's behavioral classroom engagement in middle childhood mediated the relation between early maternal stimulation and adolescent cognitive performance. Identifying pathways from earlier maternal and children's characteristics to children's later cognitive performance is an important step toward further understanding why early precursors have a long lasting impact on cognitive performance, and has implications for educational settings.